Complete Genome Sequence of Erwinia amylovora Bacteriophage vB_EamM_Ea35-70 - Yagubi, Abdelbaset I. (American Society for Microbiology, 2014)
The complete genome of an Erwinia amylovora bacteriophage, vB_EamM_Ea35-70 (Ea35-70), is 271,084 bp, encodes 318 putative proteins, and contains one tRNA. Comparative analysis with other Myoviridae genomes suggests that Ea35-70 is related to the Phikzlikevirus genus within the family Myoviridae, since 26% of Ea35-70 proteins share homology to proteins in Pseudomonas phage φKZ.